The menopausal self : identity construction and gender norms in menopause apps : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Palmerston North, New Zealand - White, Phoebe Rose (Massey University, 2024)
This thesis explored the portrayal of women, their symptoms, and experiences within menopause apps (applications, especially as downloaded by a user to a mobile device), focusing on the ideologies, perspectives, and gender norms these digital tools reinforce. Using social constructionism and Foucauldian discourse analysis, the study aimed to reveal dominant constructions of women through menopause. The primary research questions were: (1) How did menopause apps depict women's identities, symptoms, and experiences, aligning with societal norms and stereotypes surrounding menopause and femininity? (2) How did women engaging in community discussions within the apps contribute to discourses surrounding menopause? The analysis revealed that menopause apps often promoted neoliberal and post-feminist discourses, emphasising individual responsibility and empowerment, while overlooking systemic and structural factors impacting health outcomes. These apps frequently constructed menopause as a series of medical problems requiring professional intervention, perpetuating medical discourse and reinforcing traditional power dynamics between healthcare providers and patients. However, community discussion sections fostered empowerment and collaboration, encouraging women to share experiences and support each other, though this sometimes obscured the need for broader structural changes. This study highlighted the social construction of menopause within these apps, emphasising certain narratives while potentially ignoring others. It underscored the importance of critically engaging with the information provided and recognising the underlying power dynamics and biases that shape users' perceptions and behaviours. The research had limitations, including a focus on a selected sample of menopause apps and the interpretive nature of the analysis. Future research should explore a broader range of apps, incorporate diverse cultural and societal contexts, and investigate the long-term impact of using menopause apps on women's health and well-being. In conclusion, while menopause apps offered valuable support and resources, they also perpetuated specific discourses influencing users' perceptions and behaviours. By critically engaging with these apps and recognising underlying power dynamics and biases, women could navigate their menopause journey with a more informed and empowered perspective. This thesis contributed to understanding women's identity construction and health in the context of menopause apps, highlighting the need for a more supportive and equitable digital health environment for women.
Keywords: 441015 Sociology of the life course; 520304 Health psychology